Fabrication of Pyrrole‐Based Electrochemical Biosensor Platform Using Nanoimprint Lithography. Issue 8 (15th January 2018) - Ahn, Junhyoung; Kwon, Soongeun; Jung, Sanghee; Lee, Wang Sik; Jeong, Jinyoung; Lim, Hyungjun; Shin, Yong‐Beom; Lee, JaeJong
Abstract: Many electrochemical biosensors are developed and widely used for the detection of biological responses. However, there is a limitation like increasing the surface area of the working electrode for the improvement of sensitivity. Nanoimprint lithography (NIL) is a simple method that uses stamp and UV or thermally curable resins for fabricating nanopatterns and nanostructures at low cost and with high throughput and high resolution. Therefore, the fabrication of a nanostructure on the working electrode using nanoimprint lithography can improve not only the sensitivity of a biosensor to biological responses by increasing the surface area of the working electrode but also the mass production of nanopatterned electrodes. Here, a conducting polymer‐based UV‐curable resin is aimed to develop and to use it to fabricate a uniform nanostructure on the working electrode. The 150 nm pillar patterns on a Pt electrode are created using polydimethylsiloxane stamps and KIMM ANT‐6HO UV‐NIL system and measured electrochemical signals using cyclic voltammetry. Furthermore, glucose oxidase is immobilized on the conducting polymer‐imprinted electrode. The developed electrochemical biosensor successfully measures glucose levels across a dynamic range of 0.1 µg mL −1 to 200 mg mL −1 under optimized conditions. Abstract : A UV‐curable conducting polymer resin for nanoimprint lithography (NIL) is developed with pyrrole and photoinitiators. Various nanopatterns of polypyrrole are fabricated such as pillar, line, and hole nanostructures. In addition, 150 nm pillar nanostructures by UV‐NIL are patterned on Pt electrode, and glucose levels are measured in phosphate buffered saline buffer and real serum using polypyrrole‐imprinted electrode.